A supercapacitor constructed with a partially graphitized porous carbon and its performance over a wide working temperature range1. Issue 37 (7th October 2015) - Ye, Ling; Liang, Qinghua; Huang, Zheng-Hong; Lei, Yu; Zhan, Changzhen; Bai, Yu; Li, Huan; Kang, Feiyu; Yang, Quan-Hong
<x xml:space="preserve">Abstract</x> A supercapacitor constructed with a partially graphitized porous carbon exhibits high energy densities of ~46 and ~43 Wh kg−1 at 50 °C and −20 °C, respectively.